(3cJGH GdOYGeI aj JKHjJ GdEeGeIs - (3CHh WGdH jMji Hf GdMSjf Hf gGQhf GdgGQhfj,J (B404 (3g` s ((3eMeO Hf GdbGSe Hf eMeO s)
(3ChdgG (B:s
(3SCdJe habfG Gddg hEjGce EedGA cJGH ai JHUQI ePGgH GdRjOjI ai GdEeGeI Ydi EjLGR hGNJUGQ aCLHJce YdekG efi HCf CUhd gPG GdHGH hEf cGfJ ePchQI ai GdcJH , agi efJTQI ajgG s
(3BNQgG (B:s
(3hgd jchf ai fbU GdYGOI CHdZ ef Cf jNJU HTQ eeG de jNJU Hg CMO bHdg hdG HYOg Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3fSNI dfaSg eMeO Hf GdbGSe Hf eMeO s
(3cJHJ HNWjf eNJdajf s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdESdGejs